Efficacy and safety of electroacupuncture on treating mild to moderate first-episode depression: a study protocol for a randomized controlled trial - Xia, Jingyu; Jiang, Minghui; Yin, Xuan; Wang, Zuqing; Li, Feng; Wei, Haiyan; Jin, Chuanyun; Hu, Yanmei; Chen, Jianhua; Xu, Shifen (Frontiers in Psychiatry, 2025)
IntroductionOnly 30%-40% of patients with first-episode depression recover after taking antidepressants. Acupuncture is a clinically recognized treatment for depression, but its effect on first-episode depression remains unknown. This randomized controlled trial is designed to investigate the efficacy and safety of electroacupuncture (EA) compared with escitalopram (ESC) in treating patients with mild to moderate first-episode depression.Methods and analysisThis is a multi-site, single-blind, randomized controlled trial with two parallel arms. A total of 204 eligible patients will be randomly allocated to two groups: the EA group (receiving EA treatment with placebo drugs) and the ESC group (receiving escitalopram and sham acupuncture treatment). Treatment will last 12 weeks, with 3 sessions per week for the first 8 weeks, decreasing to 2 per week for the remaining 4 weeks. The primary outcome will be the score of the 17-item Hamilton Depression Rating Scale (HAMD-17), and the secondary outcomes will include depression recovery rate, depression remission rate, Patient Health Questionnaire-9 (PHQ-9), 36-Item Short Form Survey Instrument (SF-36), and the dose and frequency of ESC. The Treatment Emergent Symptom Scale (TESS) will be used to assess all adverse effects. Full details of the statistical analysis plan for the primary and secondary outcomes will be described in this article.